Profile of infection in women with vaginal discharge in North India - Sood, Nishi; Sud, Shyam Sunder (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: The objective of the present study was to observe the profile of infection in women with vaginal discharge. Methods: The present study was conducted between October 2013 and September2014. The respondents were females in reproductive age group (15-45 years) attending Obstetrics and Gynaecology OPD with history of vaginal discharge. After detailed clinical examination of the patient, pH was determined, and the posterior fornix was swabbed with a cotton tip applicator. Further a Whiff (amine) test done; wet mount was immediately prepared and examined. Another swab was sent for Gram’s stain and culture. Results: A total of 200 women with vaginal discharge were studied, of which 146 were diagnosed with pathogens. The most common form of infection was mixed infection which was diagnosed in 69 patients (34.5%). As a single pathogen, the next most common infection was Bacterial vaginosis seen in 43 patients (15.5%) and Trichomonas vaginalis seen in 3 patients (1.5%). Conclusions: The clinical manifestations of vaginits are diverse. By knowing the microbiology of the vaginal flora, we could come to the conclusion of the etiology of vaginitis.